2022
DOI: 10.1101/2022.01.28.22270004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The progressive loss of brain network fingerprints in Amyotrophic Lateral Sclerosis predicts clinical impairment

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterised by functional connectivity alterations in both motor and extra-motor brain regions. In network analysis, fingerprint represent a valid approach able to assess the subject-specific connectivity features of a given population. Here, we applied the Clinical Connectome Fingerprint (CCF) analysis to source-reconstructed magnetoencephalography (MEG) signals in a cohort of seventy-eight subjects: thirty-nine ALS patients and thirty-nine … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 47 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…We found that the spatial signatures of the most identifiable edges for individual differentiation were modified across brain states (Fig. 4-5a for alpha (8)(9)(10)(11)(12)(13) and beta frequencies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), other frequency bands reported in Supplementary Fig. 3-5).…”
Section: Spatial Meg Signatures Of Individual Differentiation Change ...mentioning
confidence: 89%
See 2 more Smart Citations
“…We found that the spatial signatures of the most identifiable edges for individual differentiation were modified across brain states (Fig. 4-5a for alpha (8)(9)(10)(11)(12)(13) and beta frequencies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), other frequency bands reported in Supplementary Fig. 3-5).…”
Section: Spatial Meg Signatures Of Individual Differentiation Change ...mentioning
confidence: 89%
“…Only very recently has the fingerprinting field started to capitalize on the spatiotemporal complexity of fast neurophysiological signals recorded from magnetoencephalography (MEG) in order to investigate neural features of individual differentiation 16,[19][20][21][22] . There are several reasons for doing so, since recorded MEG signals contain extremely rich information 23,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a Principal Component Analysis (PCA) was carried out to reduce environmental noise. Finally, we performed a supervised Independent Component Analysis (ICA) to remove physiological artefacts from the ECG (one component per participant) and the EOG (no component per participant, rarely one) (Romano et al, 2022; Rucco et al, 2022)…”
Section: Methodsmentioning
confidence: 99%
“…More recently, avalanche transition matrices have been applied to magneto/electroencephalography (M/EEG) data, in order to encapsulate the spatio-temporal spreading of neuronal avalanches on the large scale. These studies highlighted that neuronal avalanches spread preferentially across the white-matter bundles (Sorrentino et al, 2021), and that they are drastically altered in neurodegenerative diseases (Polverino et al, 2022; Romano et al, 2022, Sorrentino et al, 2021). In the context of epilepsy, the criticality framework has been used to investigate global brain dynamics during ictal and interictal epileptic activity (Osorio et al, 2009, Meisel et al, 2012, Arviv et al, 2016) showing a deviation of the system from the critical state in both conditions.…”
Section: Introductionmentioning
confidence: 99%